EFIKASI CUKA KULIT PISANG DAN AIR KELAPA SEBAGAI PENGHAMBAT Listeria monocytogenes PADA DAGING AYAM - Widaningrum Widaningrum; Miskiyah Miskiyah; Juniawati Juniawati (Jurnal Penelitian Pascapanen Pertanian, 2015)
Providing natural preservatives to increase the shelf life of chicken meat is a challenge, since the microbial contaminants problem has been a concern among many actors: government, business, consumers, and health practitioners. Acetic acid (known as vinegar) has properties as an antimicrobial, due to its ability to lower the pH and causing instability in the cell membrane of pathogenic bacteria. This paper aimed to assess the manufacture of vinegar from banana peel and coconut water as potentially natural preservative, and its application to determine the effect of microbial growth inhibition of Listeria monocytogenes in chicken meat. The study was designed using a randomized factorial design with 2 factors: 1. Types of vinegar (banana peel, coconut water, commercial acetic acid and commercial lactic acid) and 2. Storage temperature (room temperature and refrigerated temperature 5-7° C), each were repeated three times. Chicken meat that has been treated with acid soaking then stored at room temperature and cold temperatures. The results showed that banana peel and coconut water vinegar inhibit the growth of testing bacteria L. monocytogenes in chicken meat stored at room temperature more effective (5-6 log CFU/g) than the commercial acetic acid and commercial lactic acid (7-8 log CFU/g), for 24 hours storage. In chicken meat stored in cold temperatures, banana peel and coconut water vinegar had almost the same capabilities with commercial acetic acid (5.34 log CFU/g) on storage for 12 days. The most potential vinegar to be used in refrigerated temperature was banana peel vinegar.